Quality of E-KTP Services at The Population and Civil Registration Office of Majalengka Regency - Rafli Afdhalul Ichsan Kurniawan; Rizki Fauzan Fariq; Dian Andriany (Asian Journal of Social and Humanities, 2024)
Employees at the Population and Civil Registration Office (DISDUKCAPIL) of Majalengka Regency experienced several problems in serving the making of E-KTP, including, the infrastructure at the Majalengka Regency Disdukcapil was inadequate such as an unstable internet network, the number of computer devices that were still lacking, and the number of blanks that were often empty, as well as some elderly people who did not have an E-KTP because they did not understand the system. This study aims to determine the quality of service in the making of E-KTP in the Majalengka Regency Disdukcapil, according to an analysis based on the theory of Zeithami, Parasuraman, and Berry (2008) to measure good service performance referring to Law No. 24 of 2013 in which there are 5 aspects of public services, namely: service procedures, service time and completion, service costs, facilities and infrastructure. The research was carried out using a qualitative method with a descriptive approach. The results of the study show that the quality of e-KTP services at the Majalengka Regency Population and Civil Registration Office is not optimal, because there are still several problems, namely inadequate infrastructure, even though in providing E-KTP servers is quite good and in conveying information about making E-KTP, as evidenced by the active social media from the Majalengka Regency Disdukcapil.